Griever : An American Monkey King in China - Vizenor, Gerald Robert, 1934- (Book collections on Project MUSE., 1987)
Griever de Hocus, accomopanied by his rooster, Matteo Ricci, plays havoc with the monolithic institutions of the People's Republic of China in Vizenor's inspired retelling of the classic Chinese Journey to the West.